The Different Routes to Metastasis via Hypoxia-Regulated Programs. Issue 11 (November 2018) - Nobre, Ana Rita; Entenberg, David; Wang, Yarong; Condeelis, John; Aguirre-Ghiso, Julio A.
Abstract : Hypoxia is linked to metastasis; however, how it affects metastatic progression is not clear due to limited consensus in the literature. We posit that this lack of consensus is due to hypoxia being studied using different approaches, such as in vitro, primary tumor, or metastasis assays in an isolated manner. Here, we review the pros and cons of in vitro hypoxia assays, highlight in vivo studies that inform on physiological hypoxia, and review the evidence that primary tumor hypoxia might influence the fate of disseminated tumor cells (DTCs) in secondary organs. Our analysis suggests that consensus can be reached by using in vivo methods of study, which also allow better modeling of how hypoxia affects DTC fate and metastasis. Highlights: Hypoxia is associated with resistance to therapy and metastasis onset but mechanistically this link is still unclear. In vitro assays to study hypoxia in metastasis have limitations that lead to limited consensus on how it drives metastasis. New intravital imaging technologies enable studies of hypoxia and metastasis in physiological contexts, revealing unanticipated roles of hypoxia not observed in vitro . In vivo studies revealed that hypoxia could decrease motility speed while increasing invasiveness and priming tumor cells for dormancy after dissemination. In vivo analysis of hypoxia and DTC fate may reveal its link to metastasis and poor prognosis and how to prevent recurrence.